Hubungan Tingkat Literasi Kesehatan dengan Perilaku Pencegahan PTM Pada Remaja di Kabupaten Semarang - Aulia Lutfiatur Roiefah; Kartika Pertiwi; Yuliaji Siswanto (Universitas Ngudi Waluyo, 2021)
Incidence of non-communicable diseases is a health problem that causes morbidity, disability, mortality, and incurring huge costs of healthcare. The incidence of non- communicable diseases it’s not only in adults and elders, but also in the adolescent age group. Efforts to reduce the incidence rate of non-communicable diseases is the implementation behavior prevention of non-communicable diseases that are CERDIK and PHBS behavior. Improvement behavior prevention of non-communicable diseases can be influenced by health literacy level that includes of aspects access information, knowledge, understanding, and decision-making related to health information. This study was an observational analytic, with a cross-sectional design, sampling technique used Snowball sampling, total sample were 387 adolescents aged 15 – 18 years. The instrument used a questionnaire, the type of analysis was Chi-Square test Based on data analysis, there is 55% of respondents with high health literacy level, good categories for health information access (61,5%), good categories knowledge (55,3%), good categories understanding (46,3%), could take decision-related to health information (50,9%), and had a good behavior prevention of non-communicable diseases (46%). The value of chi-squares test is p = 0.000, which is a significant relationship between the health literacy level and behavior prevention for non-communicable diseases. From the results can be include that health literacy level in adolescents affects the implementation behavior prevention of non-communicable diseases.